Effects of the cross-section on the driver's behaviour approaching bicycle crossroads. (January 2021) - Bella, Francesco; Ferrante, Chiara
Highlights: To what extent is the driver's behavior at bicycle crossroad affected by the road cross-section? More critical driver yielding behaviour and braking performance on the two-lane configuration. The cross-section has the strongest effect on the logit of drivers yielding. Higher risk exposure of the cyclist crossing the two-lane configuration. The same marking scheme on the two different cross-sections is inappropriate. Abstract: This paper reports on the results of field surveys conducted at the approaching section of two bicycle crossroads in urban environment. The crossing roads are characterised by different cross-sections (one-lane and two-lane configurations) having a same marking scheme. The aim of the surveys was to evaluate the effectiveness of the specific marking scheme for the two different cross-sections and to provide relevant insight to improve the cyclist safety, based on the observed drivers' behaviours. More specifically, the data analysis was aimed at: (i) studying the yielding behaviour of the drivers on the two bicycle configurations and evaluating the effects of the observed vehicle dynamics constraints in approaching phases; (ii) analysing drivers' braking during the interaction with cyclist; (iii) defining a logistic regression model for predicting the drivers' likelihood of yielding as a function of the variables describing his behaviour and the cross-section configurations. Results have stressed out a more critical driver yielding behaviour and braking performance when approaching the bicycle crossroad on the two-lane configuration. The logistic regression model have pointed out the cross-section variable to have the strongest effect on the logit of drivers yielding, determining a significant reduction of the likelihood of yielding if the interaction driver-cyclist occurs in the two-lane configuration. Overall, the obtained outcomes highlight a higher risk exposure of the cyclist crossing the two-lane configuration. The obtained outcomes imply that the same marking scheme on the two different cross-section configurations is inappropriate. It fails to induce proper driver behaviour when he/she approaches the bicycle crossing on the two-lane configuration in order to limit the cyclist's risk exposure to the values observed on the one-lane configuration. Eventually, several measures and recommendations have been defined to reduce the risk conditions identified in two-lane configuration.